The Influence of Tutoring, Parental Attention, Self-Efficacy, Study Habits, and Learning Facilities on Student Achievement in Integrated Social Studies Subjects - Miftahul Jannah; Mona Amelia; Rika Verawati (Journal of Practice Learning and Educational Development, 2026)
This study is motivated by the importance of improving student achievement in Social Science subjects, which still shows incompleteness at SMPN 11 Sarolangun. Learning achievement is influenced by internal and external factors such as learning guidance, parental attention, self-efficacy, study habits, and learning facilities. The purpose of this study is to analyze the influence of these factors, both partially and simultaneously, on student achievement. This research employed a quantitative associative approach with a population of 82 students from grades VII and VIII, all selected using total sampling. Data were collected through validated and reliable questionnaires and documentation of students’ academic scores. Data analysis was conducted using multiple linear regression with SPSS and EViews. The results indicate that learning guidance, self-efficacy, study habits, and learning facilities significantly affect learning achievement, whereas parental attention shows a positive but not significant effect. Simultaneously, the five variables significantly influence learning achievement with an R² of 0.547, indicating that 54.7% of the variance in achievement is explained by the studied variables, while 45.3% is influenced by other factors.